(3GdeYTQGJ GddRhejIs - (3eGdc Hf YHO GdQMef Hf aQL Hf CRQb GdeUehOj GdeGdbj Hf GdeQMd , CHh GdMce,J (B699 (3g` s
(3ChdgG (B:s
(3MQa GdCda HGdJRGe Gdeje KGfjkG hGdJRGeg bHd MQa GdQhi CeG dj Edi ZjQ GdQShd eHdZ SdGekG abO Cafi GdReGf OeGA s
(3BNQgG (B:s
(3dCSeGFg aVd ade jdO bHdg oeSei HeG aj SGda GdOgQ dG dG fLRJ GdeYTQGJ GddRhejI s
(3HCYdi UaMGJgG JbWjY PgH HHYV GdCHjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B263 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B169 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B1s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B68 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(398) s
Keywords: (3GdCOHs